Patterns of gender development.[article]. - Martin, Carol Lynn
A comprehensive theory of gender development must describe and explain log-term development patterning and changes and how gender experienced in the short term. This review considers multiple views on gender patterning, illustrated with contemporary research. first, because developmental research involves in understanding normative patterns of change with age, several theoretically important topics illustrate gender development:how children come to recognize gender distinctions and understand steroetypes, and the emergence of prejudice and sexism. Second, developmental researchers study the stability of individual differences over time, which elucidates developmental process. We review stability in two domains-sex segregation and activities/interests. Finally a new approach advances understanding of developmental patterns, based on dynamic systems theory. Dynamic systems theory is a metatheoretical framework for studying stability and change, which develop from the study of complex and nolinear systems in physics and mathematics. Some major features and examples show how dynamic appraoches have been and could be applied in studying gender development